Synthesis and optimization of a selective magnetic molecular imprinted polymer toward quantification of tetracycline in food samples - Zeb, Shakeel (2023)
Tetracycline is an exceptionally important antibiotic that is frequently utilized for the treatment of bacterial disorders and respiratory conditions in both humans and animals. Both the prevention of bacterial infections and the treatment of advanced stages of bacterial growth are common applications for this antibiotic in the poultry farming industry. In order to detect tetracycline antibiotics in food samples, magnetic molecularly imprinted polymers (mag-MIP) were synthesized and tested in this work. High-performance liquid chromatography (HPLC), and fluorescence spectroscopy analysis were applied to investigate the adsorption experiments. Moreover, the tetracycline antibiotic was identified using an alternate electrochemical sensor technique. In order to make magnetic nanoparticles, iron salts like FeCl3.6H2O and FeCl2.4H2O were used; they were then modified using methacryloxypropyltrimethoxysilane (MPS). Initially, part of the research was based on HPLC and Spectro-fluorometer analysis: Magnetic nanoparticles, methacrylic acid (functional monomer), ethylene-glycol-dimethacrylate (cross-linker), and benzoyl peroxide (radical initiator) were all used in calculated proportions to synthesize the mag-imprinted polymer. In the second segment, which deals with electrochemical investigation, the mag-imprinted polymer was prepared by mixing the appropriate amount of magnetic nanoparticles, acrylic acid (functional monomer), ethylene-glycol-dimethacrylate (cross-linker), and 2,2 azo-bis-isobutyronitrile (radical initiator). The techniques of field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), and Fourier transform infrared (FTIR) were utilized in order to explore the morphological, and chemical characteristics of synthesized materials. The analytical curve was produced using the range from 1.0 × 10-5 mol L-1 to 8.0 × 10-5 mol L-1. The adsorption capacity of mag-MIP at equilibrium was 4.123 mg g-1 and adsorption process followed the Langmuir isotherm, and Temkin model and pseudo-2nd-order reaction kinetic. The proposed mag-polymer materials were applying in food samples using two different concentrations of tetracycline (1.7 × 10-5 and 2.5 × 10-5 mol L-1) obtaining recoveries ranging from 73.2-87.3% (HPLC) and 90.53–103.7% (Spectro-fluorometer), respectively. In electrochemical sensor: Tetracycline detection was carried out under optimal conditions utilizing square wave voltammetry, 15 mg of mag-MIP (on carbon paste), and the time is 80 seconds. Using this method, well-defined peaks ranging from 0.5 to 1.0 V vs. Ag/AgCl (KClsat) were produced. Analytical curves were constructed using the second peak at 0.83 V, yielding the following results: linear range of 5.0 ×10-7 to 4.0 ×10-5 mol L-1 (R2 of 0.9993), the limit of detection (LOD) of 1.5 ×10-7 µmol L-1, and repeatability of 2.82%. The results of the selectivity analysis showed that the suggested electrochemical sensor is highly efficient for tetracycline determination. The sensor was effectively used to identify tetracycline in commercial and raw milk samples, with recovery rates ranging from 93 to 103%.